2018
DOI: 10.26633/rpsp.2018.89
|View full text |Cite|
|
Sign up to set email alerts
|

Health accounts from past to present for a political arithmetic

Abstract: This report traces the progressive expansion of health accounts (HA) to measure national health expenditures, from the first attempts in 1926 by the American Medical Association to the present day. Milestones in the development of A System of Health Accounts (SHA) are covered, from the economic background to initial efforts by a few countries and organizations, to the need for a set of accounting standards for health care systems, and finally, to consolidation with SHA 2011. International organizations, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
(13 reference statements)
0
4
0
1
Order By: Relevance
“…More than 100 countries have created Health Accounts under the global standard, contributing to better understanding of health spending and financial flows (Rathe et al, 2018). However, although these accounting developments are key to monitoring progress towards WHO goals such as Universal Health Coverage, remaining challenges include improving data sources (Rathe et al, 2018).…”
Section: The Development Of the Oecd's System Of Health Accountsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 100 countries have created Health Accounts under the global standard, contributing to better understanding of health spending and financial flows (Rathe et al, 2018). However, although these accounting developments are key to monitoring progress towards WHO goals such as Universal Health Coverage, remaining challenges include improving data sources (Rathe et al, 2018).…”
Section: The Development Of the Oecd's System Of Health Accountsmentioning
confidence: 99%
“…More than 100 countries have created Health Accounts under the global standard, contributing to better understanding of health spending and financial flows (Rathe et al, 2018). However, although these accounting developments are key to monitoring progress towards WHO goals such as Universal Health Coverage, remaining challenges include improving data sources (Rathe et al, 2018). Bui et al (2015), in a systematic review of National Health Accounts (NHA) reports between 1996 and 2010 covering 117 countries, found that Health Expenditure data were often incomplete and, in some cases, of questionable quality.…”
Section: The Development Of the Oecd's System Of Health Accountsmentioning
confidence: 99%
“…National Health Accounts are used by national and international policymakers and researchers to understand the flow of expenditures for healthcare services and providers to make course corrections and set national and global goals, such as the Sustainable Development Goals and reaching Universal Health Coverage. 32 33 Unfortunately, no single resource has compiled these country-reported health expenditures, let alone attempted to estimate the admittedly large amount of missing data. This research sought out and collated 1662 country-years of health expenditure estimates from country-reported health accounts categorised into HC and HP.…”
Section: Discussionmentioning
confidence: 99%
“…In the article on health accounts, a link is made between financial accounting as a way to keep track of investments in health and policies to increase fiscal space (7). The work done on out-of-pocket expenditures in Peru shows the determinants that affect the poorest people and underscores the importance of redirecting financial protection policies to increase public expenditure (8).…”
mentioning
confidence: 99%